A method to improve the efficiency and stability of perovskite solar cells

By adding azobenzene to the perovskite precursor solution and using ultraviolet light irradiation, the problems of current voltage hysteresis and phase instability in perovskite solar cells are solved, and efficient and stable perovskite is achieved Thin film preparation improves the performance of solar cells.

CN114639782BActive Publication Date: 2025-02-14SHAANXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011483114.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-16
Publication Date
2025-02-14
Estimated Expiration
2040-12-16

AI Technical Summary

Technical Problem

There is a current-voltage hysteresis effect and phase instability in organic and inorganic hybrid perovskite solar cells, which hinder its industrialization.

Method used

Add trace amounts of photoisomerized organic macromolecule azobenzene to the perovskite precursor solution, and use ultraviolet light with wavelengths of 200-400 nm during the annealing process to regulate perovskite through photoisomerization reaction The crystallization method and crystallization rate of the crystal nucleus.

Benefits of technology

Significantly improve the crystal quality of perovskite films, increase grain size, reduce grain boundaries and defect state density, improve the efficiency and stability of solar cells, and inhibit hysteresis effects and carrier recombination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114639782B_ABST
    Figure CN114639782B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the efficiency and stability of a perovskite solar cell, wherein azobenzene is added to a perovskite precursor solution during a one-step spin coating process for preparing a perovskite film, and ultraviolet light with a wavelength of 200 to 400 nm is irradiated during annealing. The invention uses the photoisomerization property of azobenzene to regulate the microenvironment of perovskite nucleus growth by inducing its configuration change, thereby enhancing the crystallinity of the perovskite film, thereby improving the quality of the film and the photovoltaic performance of the battery, and compared with traditional perovskite solar cells, the photosensitive perovskite phase (α phase) can be effectively stabilized, and the generation of a yellow non-perovskite phase (δ phase) can be suppressed, so that the efficiency and stability of the perovskite solar cell are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a method for preparing a perovskite solar cell by optimizing a perovskite precursor solution and changing a traditional annealing method. Background Art

[0002] In recent years, organic-inorganic perovskite solar cells have developed rapidly, and the cell efficiency has soared from 3.8% in 2009 to 25.2% in 2020, and its photovoltaic performance is comparable to that of silicon-based solar cells. However, the current-voltage hysteresis effect and inherent phase instability in organic-inorganic hybrid perovskite solar cells are two key issues that hinder their industrialization.

[0003] The current-voltage hysteresis effect is related to the transport of electrons and holes, ion migration, and carrier trap capture, which are closely related to the surface morphology and crystallization quality of perovskite films. Therefore, it is necessary to develop an effective method for improving perovskite films to improve the efficiency and stability of organic-inorganic hybrid perovskite solar cells.

[0004] It is widely argued that adding trace amounts of additives to the perovskite precursor solution can control the crystallization process of the perovskite film, increase the grain size of the perovskite film, reduce the grain boundaries, and thus improve the efficiency of the device. According to previous studies, adding a small amount of alkyl halide additives to mixed halide perovskites can enhance the crystallinity of the perovskite film, greatly improving the efficiency and stability of the device; introducing highly electronegative anions on the perovskite surface or at the grain boundaries can form a stable perovskite phase by combining with organic cations through electrostatic interaction. Although the above additives can obtain high-quality perovskite films, unfortunately, by adding trace amounts of photoisomerized organic macromolecules to stabilize the α phase of the perovskite film and inhibit the formation of the δ phase, and by improving the crystallization quality of the perovskite film, there are still huge challenges to obtain a perovskite film with a larger grain size and less defect state density. Summary of the invention

[0005] The purpose of the present invention is to provide a method for obtaining a high-quality perovskite film with a larger grain size and a smaller defect state density by adding photoisomerized organic macromolecule azobenzene, thereby improving the efficiency and stability of perovskite solar cells.

[0006] For the above purpose, the preparation method of the perovskite solar cell adopted by the present invention comprises: cleaning FTO glass, chemical bath deposition of TiO2, preparing a perovskite film by a one-step spin coating method, preparing a hole transport layer on the perovskite film, and thermally evaporating a gold electrode on the hole transport layer. The method for improving the efficiency and stability of the perovskite solar cell is: in the process of preparing the perovskite film by a one-step spin coating method, azobenzene is added to the perovskite precursor solution, and irradiating with ultraviolet light with a wavelength of 200 to 400 nm while annealing.

[0007] The above-mentioned perovskite is any one of methylamido perovskite, methylamine perovskite, methylamidomethylamine perovskite, and methylamido cesium perovskite.

[0008] The amount of azobenzene added is 1% to 4% of the molar amount of the lead element in the perovskite precursor solution, and preferably the amount of azobenzene added is 2% of the molar amount of the lead element in the perovskite precursor solution.

[0009] In the above method, it is preferred that the annealing is performed while irradiating with ultraviolet light having a wavelength of 250 to 350 nm.

[0010] In the above method, the ultraviolet light irradiation time is preferably 20 to 40 minutes.

[0011] The beneficial effects of the present invention are as follows:

[0012] 1. The present invention adds a small amount of azobenzene, a macromolecular organic substance, to a perovskite precursor solution, uses chlorobenzene as an anti-solvent, and irradiates the perovskite with ultraviolet light to cause azobenzene to undergo a photoisomerization reaction under ultraviolet light to micro-regulate the crystallization mode and crystallization rate of the perovskite nucleus. The perovskite film is prepared by a one-step spin coating method, and the crystallization quality of the perovskite film is significantly improved, which is mainly manifested in an increase in grain size, a reduction in grain boundaries, and a decrease in trap state density. Compared with the unmodified perovskite film, the crystallization nucleation speed of the azobenzene-modified perovskite film is significantly faster.

[0013] 2. The photovoltaic performance of the titanium ore solar cell modified by azobenzene in the present invention has been greatly improved. Since the azobenzene-modified perovskite film has fewer grain boundaries, larger grain size and lower defect state density, the crystallization quality of the film is effectively improved, the generation of the δ phase is suppressed, the defect state density of the battery is reduced, the charge transfer speed is accelerated, and the resistance is reduced, so that the transmission performance of electrons and holes in the battery is significantly improved, which is mainly manifested in the short-circuit current and fill factor, and the opening voltage is improved. It can effectively suppress the hysteresis effect of the battery and the recombination of carriers, and contribute to the transmission and extraction of carriers at the interface of the electron transport layer / perovskite layer / hole transport layer in the battery, and finally improve the battery efficiency. And the battery can maintain a stable output of efficiency and short-circuit current under the condition of long-term light immersion in the air, and can accurately match the efficiency and short-circuit current obtained by the JV curve of the best performance battery. More importantly, the titanium ore solar cell obtained by the method of the present invention has good stability, which provides a new idea for the commercialization of perovskite batteries in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is the X-ray diffraction spectrum diagram of the perovskite film prepared in Examples 1 to 3 and Comparative Example 1.

[0015] Figure 2 It is the X-ray diffraction spectrum of the perovskite film prepared in Examples 4 to 6 and Comparative Example 1.

[0016] Figure 3 It is a half-peak width diagram corresponding to the X-ray diffraction spectrum of the perovskite thin film prepared in Examples 1 to 3 and Comparative Example 1.

[0017] Figure 4 It is a half-peak width diagram corresponding to the X-ray diffraction spectrum of the perovskite films prepared in Examples 4 to 6 and Comparative Example 1.

[0018] Figure 5 3 is the absorption diagram of the perovskite film prepared in Example 1 and Comparative Example 1.

[0019] Figure 6 2 is the band gap diagram of the perovskite films prepared in Example 1 and Comparative Example 1.

[0020] Figure 7 1 is the steady-state photoluminescence (PL) spectra of the perovskite films prepared in Example 1 and Comparative Example 1.

[0021] Figure 8 1 is the transient photoluminescence decay (TRPL) curve of the perovskite films prepared in Example 1 and Comparative Example 1.

[0022] Fig. 9 It is a typical dark state current-voltage characteristic curve of the device made of the perovskite thin film prepared in Example 1 and Comparative Example 1.

[0023] Fig.10 It is a typical dark state current-voltage characteristic curve of the device made of the perovskite film prepared in Example 2 and Comparative Example 1.

[0024] Fig.11 It is a typical dark state current-voltage characteristic curve of the device made of the perovskite film prepared in Example 3 and Comparative Example 1.

[0025] Fig.12 1 is the current density-voltage (JV) curve of the perovskite solar cells prepared in Example 1 and Comparative Example 1.

[0026] Fig.13 It is the external quantum efficiency (EQE) spectrum diagram of the perovskite solar cells prepared in Example 1 and Comparative Example 1.

[0027] Fig.14 The current density-voltage curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1 are the forward scan (from short circuit to open circuit) and reverse scan (from open circuit to short circuit).

[0028] Fig.15 It is a humidity stability diagram of the perovskite solar cells prepared in Example 1 and Comparative Example 1.

[0029] Fig.16 It is a humidity stability diagram of the perovskite solar cells prepared in Example 2 and Comparative Example 1.

[0030] Fig.17 It is a humidity stability diagram of the perovskite solar cells prepared in Example 3 and Comparative Example 1. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0032] Example 1

[0033] 1. Wipe the ordinary FTO glass with glass cleaner, and then ultrasonically clean it with ethanol, acetone, and isopropanol for 30 minutes respectively; after cleaning, blow it dry with an air compressor, and then treat it with UV-ozone plasma for 10 minutes.

[0034] 2. A TiO2 layer was deposited on the treated FTO glass by chemical bath deposition, i.e., the FTO glass was placed in a 180 mm Petri dish filled with titanium tetrachloride solution (chemically pure), deposited at 70°C for 1 hour, then rinsed with ultrapure water for 2 minutes, dried with nitrogen flow, and annealed at 200°C for 30 minutes. The thickness of the obtained TiO2 layer was about 40 nm.

[0035] 3. Dissolve 0.1611g (0.85mmol) of methylamino iodide, 0.0265g (0.15mmol) of methylamino iodide and 0.4614g (1mmol) of PbI2 in 1mL of a mixed solvent of DMF and DMSO with a volume ratio of 4:1, stir at room temperature for 6h and filter to obtain a perovskite precursor solution; in a glove box with a nitrogen atmosphere, add 0.0033g (0.02mmol) of azobenzene to the obtained perovskite precursor solution and stir evenly, then spin-coat it on the TiO2 layer, and prepare a perovskite film as a light absorption layer by a one-step spin coating method, using chlorobenzene as an anti-solvent. After spin coating, place it on a 150℃ hot stage and anneal it under 254nm ultraviolet light for 30min, and then cool it to room temperature. The thickness of the obtained perovskite film is about 450nm.

[0036] 4. In a glove box with a nitrogen atmosphere, spin-coat the spiro-OMeTAD solution at 5000 rpm for 30 seconds and deposit it on the black perovskite film to form a hole transport layer (thickness is about 240 nm). Then oxidize the spiro-OMeTAD in air for 6 hours. The Spiro-OMeTAD solution is prepared by dissolving 90 mg of Spiro-OMeTAD in a mixed solution of 36 μL of 4-tert-butylpyridine, 22 μL of 520 mg / mL lithium bistrifluoromethanesulfonyl imide (LiTFSI) acetonitrile solution and 1 mL of chlorobenzene.

[0037] 5. When the vacuum degree is 9×10 -4 The gold electrode was deposited onto the surface of the hole transport layer by thermal evaporation at 1.5 Pa, and the cell area was controlled to 0.09 cm using a metal mask. 2 , and obtain the methylamino perovskite solar cell. The thickness of the gold electrode is about 80nm.

[0038] Example 2

[0039] In step 3 of Example 1, after spin coating, the substrate was placed on a hot plate at 150° C. and annealed for 30 minutes under 310 nm ultraviolet light. The other steps were the same as in Example 1 to obtain a methylamino perovskite solar cell.

[0040] Example 3

[0041] In step 3 of Example 1, after spin coating, the substrate was placed on a hot plate at 150° C. and annealed for 30 minutes under 365 nm ultraviolet light. The other steps were the same as in Example 1 to obtain a methylamino perovskite solar cell.

[0042] Example 4

[0043] In step 3 of Example 1, 0.0017 g (0.01 mmol) of azobenzene was added to the obtained perovskite precursor solution and stirred evenly before spin coating on the TiO2 layer. The other steps were the same as in Example 1 to obtain a methylamino perovskite solar cell.

[0044] Example 5

[0045] In step 3 of Example 1, 0.0050 g (0.03 mmol) of azobenzene was added to the obtained perovskite precursor solution and stirred evenly before spin coating on the TiO2 layer. The other steps were the same as in Example 1 to obtain a methylamino-based perovskite solar cell.

[0046] Example 6

[0047] In step 3 of Example 1, 0.0066 g (0.04 mmol) of azobenzene was added to the obtained perovskite precursor solution and stirred evenly before spin coating on the TiO2 layer. The other steps were the same as in Example 1 to obtain a methylamino perovskite solar cell.

[0048] Comparative Example 1

[0049] In step 3 of Example 1, azobenzene is not added to the perovskite precursor solution, and it is directly spin-coated onto the TiO2 layer, and the perovskite film is prepared by a one-step spin coating method, chlorobenzene is used as an anti-solvent, and after the spin coating is completed, it is placed on a 150° C. hot stage for annealing for 30 minutes. The other steps are the same as in Example 1, and a methylamino-based perovskite solar cell is obtained.

[0050] The perovskite films prepared in Examples 1 to 5 and Comparative Example 1 were subjected to XRD, absorption, and steady-state photoluminescence tests. Figures 1 to 8 .Depend on Figures 1 to 4 It can be seen that compared with Comparative Example 1, the δ phase in the perovskite films prepared in Examples 1 to 5 disappears. After irradiation with ultraviolet light, the diffraction peak of the (110) crystal plane is significantly enhanced, among which the diffraction peak of the (110) crystal plane of the perovskite film in Example 1 is the strongest and the half-peak width is the smallest. This shows that the azobenzene-modified perovskite film has better crystallinity under ultraviolet light irradiation. Figure 5 , 6 It can be seen that the absorption intensity of the perovskite film of Example 1 increases significantly in the range of 500-800 nm, but the absorption edge does not change significantly and is still at 802 nm, and the corresponding band gap is 1.55 eV. Figure 7 , 8It can be seen that the PL intensity of the perovskite film of Example 1 is significantly increased, indicating that the addition of azobenzene can effectively reduce the non-radiative recombination in the perovskite film; in addition, the PL peak of the perovskite film of Example 1 is blue-shifted, indicating that the defect density of the perovskite film obtained after the addition of azobenzene is reduced. Moreover, the film has a longer carrier lifetime, which further shows that the addition of azobenzene can reduce the defect concentration in the perovskite film and slow down the recombination of carriers. In order to better prove that the defect density of the film is reduced after the addition of azobenzene, we tested the typical dark state current-voltage characteristic curve after the device was made ( Figures 9-11 ), the structure of the device is: FTO / TiO2 / FA 0.85 MA 0.15 PbI3 / PCBM / Ag, where PCBM represents [6,6]-phenyl C 61 The results show that the defect state density of the perovskite film of Comparative Example 1 and Example 1 is 2.34×10 16 cm -3 and 1.28×10 16 cm –3 The defect state density of the perovskite films of Example 2 and Example 3 is 1.42×10 16 cm –3 and 1.97×10 16 cm –3 The photovoltaic performance of the perovskite solar cells prepared in the above Examples 1 to 5 and Comparative Example 1 was further tested, and the results are shown in Figures 12 to 16 .Depend on Fig.12 It can be seen that the efficiency of the perovskite solar cell in Comparative Example 1 is 19.72%, and the short-circuit current density is 24.48 mA / cm 2 The efficiency of the perovskite solar cell in Example 1 is significantly improved to 21.98%, and its corresponding short-circuit current is 25.03 mA / cm 2 , mainly manifested in a significant improvement in the fill factor, from 72.99% to 78.49%. This is mainly due to the fact that the perovskite film with added azobenzene has fewer grain boundaries, larger grain size and lower defect state density, resulting in a significant improvement in the transmission performance of electrons and holes in the battery. In addition, the battery maintains a stable output of efficiency (PCE) and short-circuit current (Jsc) under long-term light immersion in air, and can accurately match the efficiency (PCE) and short-circuit current (Jsc) obtained by the JV curve of the best-performing device. Fig.13 It can be seen that compared with the perovskite solar cell of Comparative Example 1, the charge collection of the device of Example 1 is significantly improved in the wide wavelength range of 300-800 nm. The integrated photocurrent density of the cells of Comparative Example 1 and Example 1 is 24.05 mA / cm 2and 24.88mA / cm 2 , which is very close to the Jsc obtained in the JV curve. Fig.14 It can be seen that the addition of azobenzene can effectively inhibit the hysteresis effect of the battery, and the hysteresis coefficient of the battery is reduced from 12.3 to 4.5. This is mainly due to the reduction of the defect state density of the battery and the acceleration of charge transfer after the addition of azobenzene. When azobenzene undergoes photoisomerization reaction, it effectively reduces the resistance of the perovskite film, which significantly improves the fill factor of the battery. Moreover, the addition of azobenzene helps the transport and extraction of carriers at the interface of the electron transport layer / perovskite layer / hole transport layer in the battery, and effectively inhibits the recombination of carriers, which helps to increase the opening voltage of the battery. Therefore, the addition of azobenzene can effectively improve the crystallization quality of the film, inhibit the generation of the δ phase, and greatly improve the photovoltaic performance of perovskite solar cells, mainly including the opening voltage and fill factor. Figures 15 to 17 It can be seen that the battery of Example 1 can still maintain more than 74% of the initial efficiency after 62 days of storage in an atmosphere of 25°C and 40% relative humidity. Under the same conditions, the battery of Example 2 can maintain about 58% of the initial efficiency; the battery efficiency of Example 3 can maintain about 61% of the initial efficiency; while the battery efficiency of Comparative Example 1 decreases rapidly, only 6% of the initial efficiency. This shows that the air stability of the perovskite battery modified by azobenzene in the present invention is significantly improved.

Claims

1. A method for improving the efficiency and stability of perovskite solar cells, comprising: The method comprises cleaning FTO glass, depositing TiO2 by chemical bath, preparing a perovskite film by one-step spin coating, preparing a hole transport layer on the perovskite film, and thermally evaporating a gold electrode on the hole transport layer. The method is characterized in that during the one-step spin coating process for preparing the perovskite film, azobenzene is added to the perovskite precursor solution, and the solution is irradiated with ultraviolet light having a wavelength of 200 to 400 nm while annealing.

2. The method for improving the efficiency and stability of perovskite solar cells according to claim 1, characterized in that: The perovskite is any one of methylamido perovskite, methylamine perovskite, methylamidomethylamine perovskite and methylamido cesium perovskite.

3. The method for improving the efficiency and stability of perovskite solar cells according to claim 1, characterized in that: The added amount of azobenzene is 1% to 4% of the molar amount of the lead element in the perovskite precursor solution.

4. The method for improving the efficiency and stability of a perovskite solar cell according to claim 3, characterized in that: The amount of azobenzene added is 2% of the molar amount of the lead element in the perovskite precursor solution.

5. The method for improving the efficiency and stability of perovskite solar cells according to claim 1, characterized in that: During the annealing, ultraviolet light with a wavelength of 250 to 350 nm is irradiated.

6. The method for improving the efficiency and stability of a perovskite solar cell according to claim 1 or 5, characterized in that: The ultraviolet light irradiation time is 20 to 40 minutes.

Citation Information

Patent Citations

  • Organic and inorganic hybrid perovskite-based solar cell and method for manufacturing same

    CN104795499A

  • Method for processing electron transmission layer in perovskite solar cell via ultraviolet laser

    CN106935704A